2018
DOI: 10.1016/j.jdermsci.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The development of induced pluripotent stem cell-derived mesenchymal stem/stromal cells from normal human and RDEB epidermal keratinocytes

Abstract: We successfully established iPSC-derived MSCs from keratinocytes (KC-iPSC-MSCs) of a normal human and an RDEB patient. KC-iPSC-MSCs may have potential in therapies for RDEB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…It can be constructed from natural and/or synthetic biomaterials, either materials that remain stable in a biological environment or materials that degrade in the human body [ 2 ]. Several techniques have been adopted for their constructions, but the four main approaches that are widely used include: (i) Sheets of cells secreting ECM [ 21 ]; pre-made porous scaffolds of synthetic, natural, and biodegradable biomaterial; (ii) decellularized ECM scaffolds, and (iii) cells entrapped in hydrogels [ 9 ]. The main objective of the scaffold is to represent the matrix as similar as possible to the native ECM as all cells are in close contact with ECM, which provides structural support to cells and tissues, stimulating migration proliferation, apoptosis, survival, and differentiation [ 2 ].…”
Section: Techniques Of Skin Tissue Engineeringmentioning
confidence: 99%
“…It can be constructed from natural and/or synthetic biomaterials, either materials that remain stable in a biological environment or materials that degrade in the human body [ 2 ]. Several techniques have been adopted for their constructions, but the four main approaches that are widely used include: (i) Sheets of cells secreting ECM [ 21 ]; pre-made porous scaffolds of synthetic, natural, and biodegradable biomaterial; (ii) decellularized ECM scaffolds, and (iii) cells entrapped in hydrogels [ 9 ]. The main objective of the scaffold is to represent the matrix as similar as possible to the native ECM as all cells are in close contact with ECM, which provides structural support to cells and tissues, stimulating migration proliferation, apoptosis, survival, and differentiation [ 2 ].…”
Section: Techniques Of Skin Tissue Engineeringmentioning
confidence: 99%
“…Nakayama et al [57] successfully established hiPSC-MSC from keratinocytes of healthy individuals and patients with epidermolysis bullosa and studied their wound healing potential in a nude mouse model [57]. With subcutaneous and intravenous delivery, hiPSC-MSC successfully secreted human type VII collagen at the dermal-epidermal junction.…”
Section: Human-induced Pluripotent-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…So far, there are myriad studies confirmed improved wound healing and angiogenesis via sole‐ or co‐delivery of human iPSCs (hiPSCs)‐derived endothelial cells (ECs), SMCs, MSCs with or without fibroblasts 66,74‐80 . As an example, it was reported in the study of Shen et al that hiPSC‐derived vascular cells increased vascular formation during wound healing in Diabetic foot ulcer patient due to their high capability of differentiation to the two major vascular cell populations of endothelial cells and pericytes 81 .…”
Section: Treatment Of Chronic Wounds Using Angiogenic Approachesmentioning
confidence: 99%